Testing the Key Performance of Mobile Flood Protection System - Shoukai Chen; Huimin Li; Lei Guo; Lunyan Wang; Yongchao Cao (Advances in Civil Engineering)
Mobile flood protection systems provide a standardized flood protection method with high reliability. A comprehensive test site for mobile flood wall was established with the support of real applications, which provided opportunities to perform various tests. The anchor plate installation, seepage characteristics, and stress behavior of mobile flood protection systems were investigated through a process test, a water impounding test, and a post loading/unloading test. Test results indicated that installing anchor plates either by direct fixing or by preopened slots and eyes satisfy the construction and normal work requirements. However, the former is preferable over the latter. The mobile flood protection wall leaks when filled with water, and the leakage changes exponentially with the level. The leakage accelerates when the water level exceeds 1.5 m, thus registering 300 L/h at the 1.7 m level. In the post loading test (0–100 kN), concrete plastic deformation was first observed. Then, residual displacement was developed in the posts. The stressing process indicated that the failure process in the post, anchor plate, and base concrete system propagates from the concrete on both sides of the anchor plates toward the water side.